Acanthocephalans from freshwater fishes in northeast Thailand with the description of a new species of the subgenus Acanthosentis Verma & Dutta, 1929 (Acanthocephala, Quadrigyridae) - Olga Lisitsyna; Mikuláš Oros; Alexis Ribas; Srisupaph Poonlaphdecha; Daniel Barčák (ZooKeys)
During an ichthyoparasitological survey in northeast Thailand in 2015, four species of acanthocephalans were found in four species of freshwater fishes. Adult stages of Pallisentis rexus Wongkham & Whitfield, 1999 and Raosentis sp. (Eoacanthocephala, Quadrigyridae) were collected from Channa striata (Anabantiformes, Channidae) and Mystus mysticetus (Siluriformes, Bagridae), respectively, and cystacanths of Arhythmorhynchus sp. (Palaeacanthocephala, Polymorphidae) were found on the visceral organs of M. albolineatus (Siluriformes, Bagridae). Adult acanthocephalans of the subgenus Acanthosentis Verma & Dutta, 1929 isolated from Barbonymus schwanenfeldii (Cypriniformes, Cyprinidae) were morphologically distinct from all described species of the subgenus in the arrangement of rings of tegumental spines in two fields with a more or less pronounced distance between them, and by the presence of a dome-shaped process with a ring of small spines at the base at the posterior end in females. Molecular data were generated for three species and phylogenetic analysis based on the 18S rDNA clearly supported the generic identification of Acanthogyrus (Acanthosentis) barbonymi sp. nov. and P. rexus. While the phylogenetic position of the former species within the genus could not be clarified, the latter species formed a well-supported sister lineage in a clade with isolates of four congeneric species. Acanthogyrus (Acanthosentis) barbonymi sp. nov. is formally described, the first genetic data for P. rexus are generated, a species of the genus Raosentis Datta, 1947 is reported for the first time outside the Indian subcontinent, and a key to the species of the latter genus is presented.